PERKECAMBAHAN DAN PERTUMBUHAN TANAMAN SAWI (Brassica Juncea L.) YANG DIBERI PUPUK CAIR NUTRIFLORA DENGAN SISTEM HIDROPONIK - Sarawa, Sarawa (Jurnal Agroteknos, 2011)
ABSTRACT The research was conducted to study seedling and growth of Brassica juncea applied with nutriflora liquid Fertilizer on hydrophonix system.  The experiment has been carried out from September to December 2010 at Anduonohu, Haluoleo University Campus. The research was arranged in a randomized blocked design with three replications and five liquid fertilizer dosages; 2,5 ml L-1  water, 5,0 ml L-1  water, 7,5 ml L-1  water, 10 ml L-1 water, and 12,5 ml L-1  water.     Characters observed were seedling percentage (%), vigor index, seedling dry weight (g), number of leaf, plant height (cm), fresh weight (g), shoot root ratio, and dry weight (g). The results of research indicated seedling and growth of Brassica juncea increased with application of nutriflora liquid fertilizer on hydrophonix system. The highest fresh weight of Brassica juncea occurred with the application of 7.5 ml L-1 water of nutriflora liquid ferlizer, and the highest dry weight of Brassica juncea occurred with the application10 ml L-1  water nutriflora liquid fertilizer.  Nutriflora liquid fertilizer applied significantly correlated with the fresh and dry weights. Keywords: seedling, growth, Brassica juncea, liquid fertilizer